'Habitat' Suitability Index Mapping for Industrial Symbiosis Planning. - Jensen, Paul D.; Basson, Lauren; Hellawell, Emma E.; Leach, Matthew (Journal of Industrial Ecology, 2012)
Summary By 'working with the willing', the National Industrial Symbiosis Programme (NISP) has successfully facilitated industrial symbiosis throughout the United Kingdom and, in the process, delivered significant economic and environmental benefits for both Programme members and the country as a whole. One of the keys to NISP's success is that, unlike failed attempts to plan and construct eco-industrial systems from scratch, the Programme works largely with existing companies who have already settled in, developed, and successfully operate within a given locale. This article argues that existing and mature industrial systems provide the best prospects for identifying opportunities for, and ultimately facilitating, industrial symbiosis. Due to levels of diversification and operational fundamental niches that, in the fullness of time, develop within all industrial systems, industrially mature areas are deemed to be industrial symbiosis 'conducive environments'. Building on the conservation biology concept of a habitat suitability index, the article presents a methodology for comparing a potential site for eco-industrial development to a known baseline industrial 'habitat' already identified as being highly conducive to industrial symbiosis. The suitability index methodology is further developed and applied to a multi-criteria evaluation geographic information system to produce a 'habitat' suitability map that allows practitioners to quickly identify potential industrial symbiosis hotspots (the methodology is illustrated for England). The article concludes by providing options for the development of symbiosis suitability indices and how they can be used to support the facilitation of industrial symbiosis and regional resource efficiency.